Onuphis and Aponuphis (Annelida: Onuphidae) from southwestern Europe, with the description of a new species - Arias, Andrés; Paxton, Hannelore (Zootaxa, 2015)
This study recognises five species of Onuphis and four species of Aponuphis from southwestern Europe, represented in the Bay of Biscay, the Atlantic coasts of Iberia and the western Mediterranean Sea. One species, Onuphis anadonae sp. nov., is newly described and another species, Aponuphis willsiei Cantone & Bellan, 1996 is a new record for the Iberian Peninsula waters. Aponuphis ornata (Fauvel, 1928) and A. willsiei are shown to be tube brooders and the development of the juveniles is described. The usefulness of some Onuphis characters, as well as the size-dependent distribution of branchiae and chaetae, complicating Aponuphis species identification, are discussed. We are presenting descriptions and photographs of the distinctive Aponuphis colour pattern which we recommend as an identificatory tool instead. A dichotomous key to all species is included.